Penerapan Model Pembelajaran Advance Organizer (AO) Untuk Meningkatkan Hasil Belajar Siswa - Mika, Jahratun; Zainuddin, Zainuddin (Berkala Ilmiah Pendidikan Fisika, 2014)
The low learning results and the lack of the studentâs social skills in learning the background for this research. The general objective of this research is to describe the effectiveness of the application of learning model Advance Organizer (AO) in improving student learning outcomes of class VII-A MTs Al Huda Banjarmasin on teaching materials, which are specifically supported by (1) adherence to the lesson plan, (2) learning outcomes, (3) social skills, and (4) the interest of students towards learning. This study is an action research model of Kemmis and Mc Taggart consisting of 3 cycles. The subject is a class VII-A MTs Al Huda Banjarmasin, the teaching materials heat. Devices and instruments used are lesson plans, handouts, worksheets, THB, sheet enforceability of lesson plans, social skills observation sheets and questionnaires interest. Data obtained from the test results, observations, questionnaires, and documentation. The results showed that: (1) adherence to the RPP cycle I (good), cycle II (good), and the third cycle is very well categorized; (2) student learning outcomes in the classical category of incomplete first cycle, second cycle (complete), and cycle III (complete), (3) the first cycle of students social skills (good), second cycle (very good), and the third cycle (very good), (4) the interest of students (very interested). Be concluded that the effectiveness of the learning model Advance Organizer (AO) Uncategorized effective in improving student learning outcomes of class VII-A MTs Al Huda Banjarmasin on teaching materials heat.Â Â Â